Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/or.2016.5233
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CKIP-1 promotes tumor proliferation and cell adhesion-mediated drug resistance via regulating AKT activity in non-Hodgkins lymphoma

Abstract: Casein kinase 2 interacting protein-1 (CKIP-1; also known as PLEKHO1) is involved in regulating many processes such as cell proliferation, differentiation and apoptosis. CKIP-1 also plays an important role in many types of cancer, such as colon, breast cancer and human osteosarcoma. In the present study, we found that CKIP-1 was reversely associated with the proliferation of non-Hodgkin's lymphoma (NHL) and cell adhesion mediated drug resistance (CAM-DR). We demonstrated that knockdown of CKIP-1 promoted the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…CKIP-1 also serves a role in numerous types of cancer, including colon and breast cancers, and human osteosarcoma. Knockdown of CKIP-1 promotes proliferation of NHL cells by altering the interaction with RAC-alpha serine/threonine-protein kinase (Akt) (27). CKIP-1 inhibits macrophage proliferation through activation of Akt (28).…”
Section: Discussionmentioning
confidence: 99%
“…CKIP-1 also serves a role in numerous types of cancer, including colon and breast cancers, and human osteosarcoma. Knockdown of CKIP-1 promotes proliferation of NHL cells by altering the interaction with RAC-alpha serine/threonine-protein kinase (Akt) (27). CKIP-1 inhibits macrophage proliferation through activation of Akt (28).…”
Section: Discussionmentioning
confidence: 99%
“…The PH domain-containing casein kinase 2 interacting protein-1 (CKIP-1) was first identified as an interactive protein of casein kinase 2a (Bosc et al, 2000 ), and functions as a scaffold protein integrating multiple signaling pathways and is highly expressed in the heart under physiological functions (Ling et al, 2012 ). CKIP-1 was implicated in tumor cell proliferation (Zhu et al, 2017 ), muscle cell differentiation (Safi et al, 2004 ), cell apoptosis (Zhang et al, 2005 ), the regulation of cell morphology (Canton et al, 2006 ), and the actin cytoskeleton (Canton et al, 2005 ). We previously showed that CKIP-1 functioned as a novel regulator of pathological cardiac remodeling induced by pressure overload (Ling et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 CKIP-1 might function as a potential tumour suppressor gene in these malignancies. 5,8,9 In contrast to these previous reports, another study demonstrated that CKIP-1 mRNA was highly expressed in non-small cell lung cancer tissue and that CKIP-1 knockdown could promote cell apoptosis and inhibit tumour cell growth. 7 Although CKIP-1 has been studied in several types of tumour, the expression levels and the possible role of CKIP-1 in the intestinal type of GC remains unclear.…”
Section: Discussionmentioning
confidence: 59%
“…[14][15][16] Recently, the role of CKIP-1 in malignancies has attracted more attention. For example, studies have shown that CKIP-1 is a scaffold protein that may be involved in the tumorigenesis and progression of colorectal cancer, 5 non-Hodgkin's lymphoma 8 and glioma. 9 CKIP-1 might function as a potential tumour suppressor gene in these malignancies.…”
Section: Discussionmentioning
confidence: 99%